An englishwoman in the Alentejo Edith Guest and the study of megalithism in Portugal in the 1930s - Melo, Ana Ávila de (2019)
In 1934 English archaeologist Edith Guest (1873–1942) visited the Alentejo region in south-central Portugal. Though not of the first rank of famous archaeologists, Guest made a contribution to archaeology in the first half of the twentieth century, assisting such luminaries as Margaret Murray (1863–1963) and Gertrude Caton-Thompson (1888–1985) in their excavations in the Mediterranean. But why did Guest visit the megaliths in the Alentejo region of Portugal in 1934? Based on unpublished contemporary sources, such as diaries, letters and photographs, this paper suggests that Guest’s presence on the Iberian Peninsula was linked to the ambitions of Manuel Heleno (1894–1970), the second director of the National Archaeological Museum in Lisbon. Studies on megalithic Alentejo were at this time still in their infancy, and Heleno hoped to raise the profile of such studies and the museum with an enterprising schedule of excavations that would attract notable archaeologists and the ensuing publicity. Heleno’s aspirations were successful: archaeologists such as Hugo Obermaier, Vera and Georg Leisner and, of course, Edith Guest took an interest in the fieldwork, helping to bring it to wider attention in Portugal and elsewhere.